Odpowiedzi

2010-02-22T18:01:48+01:00
A)2*3-2+6+7*2=6+8+14=28
b)2*5+0,1-3*5+4*0,1-1=10+0,1-15+0,4=-4,5
c)13*0,2-2*(-1)+7-9*0,2+(-1)-4+0,2-3=2,6+2+7-1,8-1-4+0,2-3=8
1 3 1
2010-02-22T18:07:56+01:00
A) 2a+3-a+6+7a= dla a=-2
=2a-a+7a+3+6=8a+9=8*(-2)+9=-16+9=-7
b)2z+t-3z+4t-1= dla z=5 i t= 0,1
=2z-3z+t+4t-1=-z+5t-1=-5+5*0,1-1=-5+0,5-1=-5,5
c)13x-2y+7-9x+y-4+x-3= dla x=0,2 i y = -1
=13x-9x+x-2y+y+7-4-3=4x-y=5*0,2-(-1)=1+1=2
d)n²+n-7+3n²-n-9-n+16= dla n =-½
=n²+3n²+n-n-n-7-9+16=4n²-n=4*(-½)²-(-½)=4*¹/₄+½=1+½=1½
1 5 1